Matching caricatures to photographs. Issue 1 (December 2015) - Abaci, Bahri; Akgul, Tayfun
Abstract Facial caricatures are informative funny images that allow us to identify a subject even with a few lines and dots. Matching caricatures to photographs is a challenging cross-modal face matching problem. This paper addresses this problem by defining a set of qualitative face features both for caricatures and photographs where features are automatically extracted from photos and manually labeled in caricatures. Additionally we release a publicly available caricature-photograph database with 200 caricatures and corresponding photomates. In our experiments, we use genetic algorithms and logistic regression and achieve over 30.0 % 30.0 % recognition rate at 0.1 false accept rate.